EDUCATION OF TECHNICAL DESIGN USING COMPUTER TECHNOLOGY AT THE PRIMARY SCHOOL - HODIS, Zdeněk; VYBÍRAL, Petr; HRBÁČEK, Jiří; KUČERA, Martin; VINKLOVÁ, Sylva (Trends in education, 2014)
This contribution shows the use of computers for teaching the fundamentals of technical drawing at the primary school. Within information technology were pupils at primary schools Mšec introduced the ability to create graphical drawings using specialized CAD program. Students become familiar with the basic program commands progeCAD and basics of drawing in this program. Form a group of the interview were collected knowledge on the issue of CAD and were subsequently analyzed results of interviews.
Keywords: Information Technology; CAD; Education at the Primary School.